(untitled) (Global Journal of Human-Social Science, 2019)
This paper is focused on health and hygiene practice of tea garden workers in Bangladesh. It is generated out of a study conducted in a tea garden of Sylhet City in Bangladesh. The tea garden workers are mostly vulnerable as they deprived from proper health, hygiene and sanitation. They are badly treated in every respect of their life. To explore the health and hygiene facilities, culture of practice, diseases due to not having proper practices and health supports from Government and Non-government organizations, the study approach was qualitative in nature and case study method considered as method. By using purposive sampling method fifteen (15) respondents were selected from the study area. Semi-structured interview schedule and observation technique were used to collect primary data from the respondents. It was found that majority of the tea garden workers and their family members are now aware about health and hygiene practice. They are suffering from different types of general and chronic illnesses like jaundice, diarrhea, skin etc. Most of the family of tea gardens drink tube-well water and use the same for bathing, washing and other household purposes.